Laboratory Simulation of Flow through Rough-Walled Microfractures under High Hydraulic Gradient - Shuai Zhang; Wei-Guo Qiao; Yan-Zhi Li; Wei-Jie Song; Jun-Ling Qin; Ji-Yao Wang (Geofluids)
Laboratory experiments on fluid flow through fracture are important in solving the fluid-in-rush problems that happen during the tunnel excavation. In order to study the mechanism of fluid flow through a rough-walled microfracture, fluid flow experiments were carried out and the fiber Bragg grating (FBG) strain sensors were applied to monitor the deformation of the microfracture surface during the seepage process. Considering the difficulty of collection of undisturbed rock samples from the deep locations, a methodology to simulate fluid flow through a fractured rock mass using analog materials containing a single fracture was developed. This method is easy to simulate the fluid flow through a fracture of certain aperture. Experimental data showed that Forchheimer equation could provide an excellent description of the nonlinear relationship between hydraulic gradient and flow velocity, and the variations of Forchheimer coefficients with joint roughness coefficient (JRC) were studied. It was found that the deformation of the microfracture surface subjected to seepage could be accurately captured by the quasi-distributed FBG strain sensors. The test results also demonstrated that the surface strain is significantly affected by hydraulic pressure.